2007
DOI: 10.1073/pnas.0608361104
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns and determinants of vascular plant diversity

Abstract: Plants, with an estimated 300,000 species, provide crucial primary production and ecosystem structure. To date, our quantitative understanding of diversity gradients of megadiverse clades such as plants has been hampered by the paucity of distribution data. Here, we investigate the global-scale species-richness pattern of vascular plants and examine its environmental and potential historical determinants. Across 1,032 geographic regions worldwide, potential evapotranspiration, the number of wet days per year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

91
1,205
12
15

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,165 publications
(1,370 citation statements)
references
References 44 publications
(76 reference statements)
91
1,205
12
15
Order By: Relevance
“…It is unlikely that a single model explains the patterns that influence species diversity for any group of organisms in different ecosystems. Many hypotheses resulting from meta studies explain the distribution and patterns of species richness of birds (Davies et al 2007;Rahbek et al 2007), vascular plants (Kreft and Jetz 2007), and plants and animals (Hawkins et al 2007;Whittaker et al 2007), but none of these studies took fungi into account. The number of macrofungal species on its own is not a good parameter to estimate the ecological quality of mycobiota occurring in Amazon forests.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that a single model explains the patterns that influence species diversity for any group of organisms in different ecosystems. Many hypotheses resulting from meta studies explain the distribution and patterns of species richness of birds (Davies et al 2007;Rahbek et al 2007), vascular plants (Kreft and Jetz 2007), and plants and animals (Hawkins et al 2007;Whittaker et al 2007), but none of these studies took fungi into account. The number of macrofungal species on its own is not a good parameter to estimate the ecological quality of mycobiota occurring in Amazon forests.…”
Section: Discussionmentioning
confidence: 99%
“…Direct modelling of the impact of angiosperms under Cretaceous conditions is needed, but it is notable that the fossil record indicates at least seasonal aridity was widespread in the Cretaceous at both tropical and temperate latitudes, while vegetation consistent with ever-wet conditions was well established at similar temperatures at both tropical and temperate latitudes after the rise of angiosperm ecological dominance ( Although patterns within subgroups can be complex (Punyasena et al 2008), the diversities of tropical plants, invertebrates and vertebrates are fostered by abundance of rainfall, evenness of rainfall and the broad geographical extent of rainforests (Reed & Fleagle 1995;Kleidon & Mooney 2000;Hawkins et al 2003;Leigh et al 2004;Jaramillo et al 2006;Kreft & Jetz 2007)-all shown here to be bolstered by the high transpiration rates of the angiosperms. For example, if the particularly strong correlation between tropical plant diversity and number of wet days (Kreft & Jetz 2007) is taken at face value-not including other important factors such as regional history, geography and nutrient dynamics in determining plant diversitythen 50 per cent reductions in local plant diversities would be expected to accompany the average loss of 86 wet days per year in the eastern part of the Amazon when angiosperm vegetation is replaced (figure 5). Thus, in no small part, angiosperm tropical diversity is the result of the ecosystem modifications initiated by the hydraulic physiology of angiosperms themselves.…”
Section: Discussionmentioning
confidence: 99%
“…It considerably extends univariate and sometimes narrative approaches that examine the fit of the observed patterns to only single explanatory models or mechanisms (for example, in Madagascar 27,29,38 ) or compare a limited number of competing variables in univariate approaches 32 . Such analyses might be hampered by spatial autocorrelation of biodiversity patterns and predictor variables thereby inflating type-I errors in traditional statistical tests 39,40 . Spatial autocorrelation can be excluded from models 41 as a predictive parameter [42][43][44] or by incorporating the spatial dependence into the covariance structure 44 , as was applied in this study.…”
Section: Discussionmentioning
confidence: 99%